Historical newspapers unlock new insights into the evolution of seafood value chains in Brazil - Herbst, Dannieli Firme; Gerhardinger, Leopoldo Cavaleri; Brugere, Cecile; Macedo, Thais Peixoto; Silva, Luiz Geraldo; Colonese, André Carlo (Frontiers in Sustainable Food Systems, 2024)
Introduction This study examines the understudied historical evolution of the seafood value chain in southern Brazil by analysing newspaper articles from Santa Catarina state, published between 1855 and 2019. Methods Through a meticulous review of 598 selected articles, we reconstruct the development and transformation of small-scale fisheries (SSF) and their interaction with the emerging industrial fishing sector. Results and discussion Our findings highlight the central role of SSF in the seafood value chain, contributing significantly to production, processing, retail, and trade, despite increasing competition and challenges from industrial fishing and aquaculture. The analysis reveals shifts in fish species targeted, processing methods employed, market dynamics, and consumption patterns over time. Notably, the study uncovers the resilience and adaptability of SSF in maintaining their importance to local economies and food security, amidst technological, economic, and regulatory changes. Furthermore, it underscores the often-overlooked contributions of women in seafood value chains, advocating for their equitable recognition. By providing a comprehensive and multi-faceted historical perspective, this research can inform contemporary policy-making, aiming to foster more resilient, inclusive, and sustainable seafood value chains in Brazil.